2023
DOI: 10.3390/nano13040720
|View full text |Cite
|
Sign up to set email alerts
|

Ingested Polystyrene Nanospheres Translocate to Placenta and Fetal Tissues in Pregnant Rats: Potential Health Implications

Abstract: Recent studies in experimental animals found that oral exposure to micro- and nano-plastics (MNPs) during pregnancy had multiple adverse effects on outcomes and progeny, although no study has yet identified the translocation of ingested MNPs to the placenta or fetal tissues, which might account for those effects. We therefore assessed the placental and fetal translocation of ingested nanoscale polystyrene MNPs in pregnant rats. Sprague Dawley rats (N = 5) were gavaged on gestational day 19 with 10 mL/kg of 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A combination of in vitro , animal, and human ex vivo studies demonstrate placental cell uptake of MNPs is enhanced by smaller size and greater concentration ( 106 112 ). Observations in both maternal mice and rats exposed to PS-NPs during gestation, ranging in size from 20 to 500nm, demonstrated the presence of these particles in fetal liver ( 96 , 108 , 109 ), heart ( 96 , 109 ), brain ( 99 , 108 , 109 ), lung ( 108 , 109 ), and kidney ( 109 ). Interestingly, a similar exposure using PE-MPs (10-45µm) resulted in MP accumulation exclusively in fetal kidneys ( 110 ).…”
Section: Mnp Exposure In Pregnancymentioning
confidence: 99%
“…A combination of in vitro , animal, and human ex vivo studies demonstrate placental cell uptake of MNPs is enhanced by smaller size and greater concentration ( 106 112 ). Observations in both maternal mice and rats exposed to PS-NPs during gestation, ranging in size from 20 to 500nm, demonstrated the presence of these particles in fetal liver ( 96 , 108 , 109 ), heart ( 96 , 109 ), brain ( 99 , 108 , 109 ), lung ( 108 , 109 ), and kidney ( 109 ). Interestingly, a similar exposure using PE-MPs (10-45µm) resulted in MP accumulation exclusively in fetal kidneys ( 110 ).…”
Section: Mnp Exposure In Pregnancymentioning
confidence: 99%
“…Recent work has shown the presence of nanoplastics and microplastics within the human placenta, and nanoplastics have been observed to cause damage to developing mammalian fetuses. [125][126][127][128] Our findings can instruct the design of more biocompatible PCL and other biomaterials, in general, by applying new approach methodologies and non-targeted bioassays to assess biocompatibility. [129][130][131] Zebrafish have been demonstrated as effective platforms for studying the foreign body response to biomaterials and developing engineered tissues because of their optically transparent transgenic lines and rapid development.…”
Section: Biomedicalmentioning
confidence: 99%
“…Exposing animals to MPs via the oral gastric route leads to the dissemination of MPs outside of the intestine, specifically the liver. 60 Additionally, several studies in humans, mice, chickens, rats, and zebrafish have shown MP and nanoplastic (NP) ingestion results in their accumulation in tissues such as the placenta, 61 liver, 48 , 57 and kidney. 62 , 63 The distribution into the liver caused metabolic changes in mice 30 , 61 and fish.…”
Section: Introductionmentioning
confidence: 99%
“… 60 Additionally, several studies in humans, mice, chickens, rats, and zebrafish have shown MP and nanoplastic (NP) ingestion results in their accumulation in tissues such as the placenta, 61 liver, 48 , 57 and kidney. 62 , 63 The distribution into the liver caused metabolic changes in mice 30 , 61 and fish. 34 , 64 , 65 These studies highlight how MPs can cross the intestinal barrier and can cause extraintestinal manifestations (e.g., inflammation and oxidative stress).…”
Section: Introductionmentioning
confidence: 99%